1988
DOI: 10.1021/bi00421a038
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy of 13C:O labeled phospholipids hydrogen bonding to carbonyl groups

Abstract: Fourier transform infrared spectroscopy has been used to characterize the carbonyl stretching vibration of DMPC, DMPE, DMPG, and DMPA, all labeled with 13C at the carbonyl group of the sn-2 chain. Due to the vibrational isotope effect, the 13C = O and the 12C = O vibrational bands are separated by ca. 40-43 cm-1. This frequency difference does not change when the labeling is reversed with the 13C = O group at the sn-1 chain. For lipids in organic solvents possible conformational differences between the sn-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
360
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(400 citation statements)
references
References 47 publications
(32 reference statements)
33
360
1
1
Order By: Relevance
“…2 A). The elongation of these resonances along the diagonal direction of the 2D IR spectrum confirms the inhomogeneous character of the absorption bands of the carbonyl moieties (10,11,16). Each resonance has a negative (blue) contribution due to ground-state bleaching and to stimulated emission from the first excited state and a Author contributions: V…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…2 A). The elongation of these resonances along the diagonal direction of the 2D IR spectrum confirms the inhomogeneous character of the absorption bands of the carbonyl moieties (10,11,16). Each resonance has a negative (blue) contribution due to ground-state bleaching and to stimulated emission from the first excited state and a Author contributions: V…”
mentioning
confidence: 66%
“…The carbonyl stretching line-shapes in membranes could yield direct information about molecular architecture and fluctuations in the membrane interface (10, 11), provided that the origin of the spectral inhomogeneity of the carbonyl IR response in phospholipid membranes is understood. The inhomogeneity was attributed to differences in the local environment of the sn-1 and sn-2 carbonyl moieties stemming from the packing arrangements (6, 8), the local chain conformations (8,9,(12)(13)(14), the relative positions of the two CAO groups with respect to the interface (9, 15), and the degree of hydration (16,17). In an elegant work, Blume et al (16) ruled out all of the scenarios involving local structural differences except hydrogen bonding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the use of fully hydrated, specifically 13 C O labelled phospholipid bilayers, this assignment was questioned, since, should the two bands correspond to the sn-1 and sn-2 carbonyls, their maxima should not be more than 4 cm − 1 apart. In fact, 13 C labelling of only one the positions still gave rise to two bands around 1743 and 1728 cm − 1 (Blume et al, 1988;Lewis and McElhaney, 1992). These studies concluded that the underlying components normally resolved in the stretching vibrations of C O absorption bands are the summation of comparable contributions from both of the ester carbonyl groups and assigned to subpopulations of free and hydrogenbonded ester carbonyl groups.…”
Section: The Interfacial Regionmentioning
confidence: 88%
“…The decrease in the frequency indicates a strengthening of the hydrogen bonds or even a formation of new hydrogen bonds between the components Korkmaz and Severcan, (2005). Also, the degree of hydrogen-bond formation was monitored in the glycerol backbone region of the DPPC molecule by changes in the contours of the ester C=O stretching bands Blume et al (1988). …”
Section: Transmission Electron Microscopymentioning
confidence: 99%